Development and validation of the Perceived Game-Specific Soccer Competence Scale - Forsman, H.; Gråstén, A.; Blomqvist, M.; Davids, K.; Liukkonen, J.; Konttinen.N. (Journal of Sports Sciences, 2016)
The objective of this study was to create a valid, self-reported, game-specific soccer competence scale. A structural model of perceived competence, performance measures and motivation was tested as the basis for the scale. A total of 1321 soccer players (261 females, 1060 males) ranging from 12 to 15 years (13.4 ± 1.0 years) participated in the study. They completed the Perceived Game-Specific Soccer Competence Scale (PGSSCS), self-assessments of tactical skills and motivation, as well as technical and speed and agility tests. Results of factor analyses, tests of internal consistency and correlations between PGSSCS subscales, performance measures and motivation supported the reliability and validity of the PGSSCS. The scale can be considered a suitable instrument to assess perceived game-specific competence among young soccer players.